Safety of monoclonal antibodies and related therapeutic proteins for the treatment of neovascular macular degeneration: addressing outstanding issues. Issue 1 (2nd January 2016) - Ziemssen, Focke; Sobolewska, Bianka; Deissler, Heidrun; Deissler, Helmut
Abstract : Introduction : The vascular endothelial growth factor (VEGF) inhibitors most widely used to treat neovascular age-dependent macular degeneration (nAMD) are different proteins with structural features potentially relevant to adverse effects (AEs). Two of these are also established in cancer therapy (with higher dosages and AEs). The importance of ocular AE and extraocular activities is still a subject of controversy and ongoing research. Areas covered : Potential risks of intraocular VEGF inhibition based on prospective studies, in vitro investigations, pharmacokinetics, and hints from anti-cancer treatment. Expert opinion : nAMD is a frequently observed chronic clinical condition severely affecting the visual function of elderly persons. Intravitreal injection of VEGF-inactivating proteins is highly effective to prevent loss of vision. Anti-VEGF therapy is well tolerated, and low rates of ocular and systemic AEs in smaller trials suggest a very high benefit/risk ratio. The proteins established in nAMD therapy show similar efficacies. In the controversy over the off-label use of bevacizumab purely on grounds of much lower cost, the small, but potentially relevant differences between the available drugs are easily either dramatized (by pharmaceutical companies) or trivialized (by health insurances) and even political interference is involved. Facing the lack of a convincing body of evidence regarding safety, further long-term study results seem necessary.